The intersection of intellectual and developmental disabilities and HIV: A scoping review. Issue 3 (3rd July 2019) - Jung, James K. H.; Heifetz, Marina; Durbin, Anna; Lunsky, Yona
ABSTRACT: Background: HIV among individuals with intellectual and developmental disabilities (IDD) is rarely studied. This scoping review examined the HIV prevalence, health service use, prevention and risk behaviours among individuals with IDD. Method: Journal articles, book chapters and theses written in English and published from 1991 to 2017 in four academic databases (PubMed, PsycINFO, CINAHL and Web of Science) were eligible for inclusion. Results: From 1636 unique records, 32 documents were included in this review. They contained limited information on HIV prevalence and health service use by individuals with IDD and HIV. Most studies identified a poor understanding of HIV and high-risk behaviours, such as inconsistent condom use, among individuals with IDD. While HIV education programs were effective for this population, no studies identified educational interventions for their service providers. Conclusion: There is a need for educational programs and policies on HIV for both service providers and individuals with IDD.